Effect of some volatile compound on some deuteromycetean fungi - S, Dandge Vidya (Recent Research in Science and Technology, 2012)
Fungi respond to various volatile compounds in their ability to grow and reproduce. However, this aspect of fungal metabolism has been relatively less attended to. In the present investigation effects of certain volatile compounds on the growth and sporulation of four species of Curvularia, three species of Fusarium, two species of Phoma and Botryodiplodia sp. have been studied. C. lunata. & C. senegalensis showed poor growth in acetic acid, ethyl alcohol, n-butanol, propionic acid, phenol, toluene, formaldehyde; C. prasadii & C. clavata showed good to moderate growth except in acetic acid & phenol. Three species of Fusarium showed good to moderate growth in acetone, ethyl alcohol, phenol & toluene, formaldehyde & inhibited in acetic acid, n-butanol, propionic acid. In Phoma excellent growth was seen in acetone, good in ethyl alcohol, moderate to poor in toluene, formaldehyde, acetic acid, phenol while inhibited in propionic acid & butanol. In B. theobromae excellent growth was seen in acetone, good in ethyl alcohol, moderate in acetic acid, toluene & inhibited in propionic acid, butanol, phenol & formaldehyde.